Luck and skill in professional League of Legends (E-sports) - Douglas, C. (Massachusetts Institute of Technology, 2018)
As professional gaming (e-sports) develops a greater global infrastructure, it will be critical to create league systems in which skill and luck balance to create competitive, exciting, and fair environments. This study uses the most developed e-sport leagues, found in the game League of Legends (LoL), to examine early efforts at crafting such environments. The use of "winning persistence" and Bayesian statistical analyses reveal that best-of-one matches in LoL demonstrate an overall luck-skill ratio similar to professional baseball (MLB) and football (NFL). Best-of-three matches exhibit an understandably higher ratio of skill, similar to professional basketball (NBA). With both match lengths exhibiting viable but significantly different luck-skill ratios, LoL creator, Riot Games has the tools to control how much luck and skill exist in their matches and leagues, setting an important precedent for future leagues and organizations.